2018
DOI: 10.1186/s12870-018-1314-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the regulatory networks of cytokinin in promoting the floral feminization in the oil plant Sapium sebiferum

Abstract: BackgroundSapium sebiferum, whose seeds contain high level of fatty acids, has been considered as one of the most important oil plants. However, the high male to female flower ratio limited the seed yield improvement and its industrial potentials. Thus, the study of the sex determination in S. sebiferum is of significant importance in increasing the seed yield.ResultsIn this study, we demonstrated that in S. sebiferum, cytokinin (CK) had strong feminization effects on the floral development. Exogenous applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…This correlated well with other studies that other GA biosynthesis inhibitors such as PAC, uniconazole, and Pro-Ca increase CK levels in different plant tissues (Grossmann et al, 1994;Upreti et al, 2013;Liu et al, 2015). Active CKs are degraded mainly by CKX, which can be induced by exogenous CK (6-BA) owing to feedback mechanisms (Kieber and Schaller, 2018;Ni et al, 2018). Therefore, the MC mediated upregulation of CKX1, CKX6, and CKX7 might be attributed to the increased CK levels in cotton internodes.…”
Section: Remarkably Altered the Biosynthesis And Signaling Transdusupporting
confidence: 90%
See 1 more Smart Citation
“…This correlated well with other studies that other GA biosynthesis inhibitors such as PAC, uniconazole, and Pro-Ca increase CK levels in different plant tissues (Grossmann et al, 1994;Upreti et al, 2013;Liu et al, 2015). Active CKs are degraded mainly by CKX, which can be induced by exogenous CK (6-BA) owing to feedback mechanisms (Kieber and Schaller, 2018;Ni et al, 2018). Therefore, the MC mediated upregulation of CKX1, CKX6, and CKX7 might be attributed to the increased CK levels in cotton internodes.…”
Section: Remarkably Altered the Biosynthesis And Signaling Transdusupporting
confidence: 90%
“…Some important TFs are shown in Figure S6. Most of the MYBs were downregulated, including genes functioning in plant circadian clock and ABA accumulation (Adams et al, 2018) and those associated with the ABA signal pathway (Ni et al, 2018). The bHLH TFs play important roles in the control of cell elongation.…”
Section: Differentially Expressed Tfsmentioning
confidence: 99%
“…Accumulated studies indicated that signi cant difference in CTK was usually detected between male and female owers [55,56,57]. For example, treatment with exogenous CTKon Mercurialis annua L., a dioecious plant led the ower primordia to differentiate into pistil [55].…”
Section: Mirna Regulating Ctk Signal Transduction Pathway Affects Sexmentioning
confidence: 99%
“…APT proteins participate in cytokinin inactivation (Allen et al, 2002;Zhang et al, 2013). Cytokinins are involved in flower development and the regulation of the number of ovules per pistil, gynoecium size (Bartrina et al, 2011;Marsch-Martínez et al, 2012), and flower sex specification (Durand and Durand, 1991;Ni et al, 2018). In grapevine, cytokinin application restores normal female organ development, producing berries from male grapevine flowers (Negi and Olmo, 1966).…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hmentioning
confidence: 99%